Believing and social interactions: effects on bodily expressions and personal narratives - Seitz, Rüdiger J.; Angel, Hans-Ferdinand; Paloutzian, Raymond F.; Taves, Ann (Frontiers in Behavioral Neuroscience, 2022)
The processes of believing integrate external perceptual information from the environment with internal emotional states and prior experience to generate probabilistic neural representations of events, i.e., beliefs. As the perceptual information and the emotional valence of past events may change over time, their representations change in memory. Although these neural representations manifest mostly below the level of a person’s conscious awareness, they may nevertheless inadvertently affect the person’s bodily expressions and prospective behavior. By yet to be understood mechanisms people can become aware of these representations and describe and reflect upon them. Typically, people can communicate the content of their beliefs as personal statements and can summarize the narratives of others to themselves or to other people. Social interactions may benefit from the consistency between a person’s bodily expressions and verbal statements, because the person appears authentic and ultimately trustworthy. The transmission of narratives can thus lay the groundwork for social cooperation within and between groups and, ultimately, between communities and nations. Conversely, a discrepancy between bodily expressions and narratives may cause distrust in the addressee(s) and eventually may destroy social bonds.